AKTIVITAS KEAGAMAAN DI KALANGAN MAHASISWA PERGURUAN TINGGI UMUM - Ali Said Damanil; Ida Ruwaida (Badan Litbang dan Diklat Kementerian Agama RI, 2005)
This article, which is the summary and moderation of research results, is a description of the pattern of religious activities, especially religious instruction models in the religious groups of students on the campus of general higher learning institutions. This article also concerns with material coverage and the selection of study methods, including the symbols of instruction as well as sources used as instructional reference. Factors relating to the instructional models are also sufficiently explored in this article.